1999
DOI: 10.1038/sj.bjp.0702786
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non‐adrenergic, non‐cholinergic inhibitory responses of the isolated guinea‐pig trachea: differences between pre‐ and post‐ganglionic nerve stimulation

Abstract: 1 Di erences in the mechanism of non-adrenergic, non-cholinergic (NANC) inhibitory responses to preganglionic-and post-ganglionic nerve stimulation were investigated in the guinea-pig isolated trachea. 2 Stimulation of the vagus nerve at frequencies above 4 Hz elicited NANC relaxation of the trachealis muscle. Responses to low frequencies of stimulation (4 ± 8 Hz) were abolished by the nitric oxide (NO) synthase inhibitor L-NOARG (10 mM), while a L-NOARG resistant component was observed at higher stimulus freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
(52 reference statements)
1
15
0
Order By: Relevance
“…Although high voltage (10-20 V) efferent vagal stimulation has usually been associated with bronchoconstriction, we have shown that low voltage vagal stimulation can inhibit airway bronchoconstriction in addition to increasing HR and blood pressure. The mechanism is unclear, but in isolated guinea pig trachea, efferent VNS-induced NANC inhibition (46) was frequency dependent with the maximal inhibition at 32 Hz and similar to our signal. Alternatively, the afferent vagal nerve has been linked with activation of the SNS with either adrenergic nerve (42) or iNANC nerves (47) mediating relaxation in response to histamine.…”
Section: Discussionsupporting
confidence: 77%
“…Although high voltage (10-20 V) efferent vagal stimulation has usually been associated with bronchoconstriction, we have shown that low voltage vagal stimulation can inhibit airway bronchoconstriction in addition to increasing HR and blood pressure. The mechanism is unclear, but in isolated guinea pig trachea, efferent VNS-induced NANC inhibition (46) was frequency dependent with the maximal inhibition at 32 Hz and similar to our signal. Alternatively, the afferent vagal nerve has been linked with activation of the SNS with either adrenergic nerve (42) or iNANC nerves (47) mediating relaxation in response to histamine.…”
Section: Discussionsupporting
confidence: 77%
“…This suggested that a neuropeptide might mediate these responses since neuropeptides are known to be released following high frequency stimulation (Lundberg, 1996). Indeed, the peptidase α‐chymotrypsin has been shown to attenuate the responses in the guinea‐pig trachea (Moffatt et al ., 1999) and in the female pig urethra (Werkström et al ., 1997). In the current study non‐nitrergic NANC responses in the rabbit vaginal wall were inhibited with TTX and were greater in magnitude and duration at high frequencies, as in the pig urethra and guinea‐pig trachea, thus we hypothesized that they were mediated by a neuropeptide.…”
Section: Discussionmentioning
confidence: 96%
“…In this tissue high frequency stimulation (>12 Hz) elicited non‐nitrergic NANC relaxation responses (Werkström et al ., 1995). Similar responses have been reported in the guinea‐pig trachea (Moffatt et al ., 1999). This suggested that a neuropeptide might mediate these responses since neuropeptides are known to be released following high frequency stimulation (Lundberg, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β ‐Adrenergic receptors contribute to pulmonary artery (PA) vasorelaxation by activation of pulmonary vascular smooth muscle adenylate cyclase (Fullerton, Hahn, Banerjee & Harken, 1994; Fullerton, Agrafojo & Mcintyre, 1996). In addition to β ‐adrenoceptor‐mediated responses, it is known that stimulation of the autonomic nerves to several organs causes responses which are neither adrenergic nor cholinergic (Gibson, Mirzazadeh, Hobbs & Moore, 1990; Postorino, Serio & Mule, 1995; Kubota, Hamasaki, Sata, Saga & Said, 1988; Moffatt, 1999; Gumusel, Orhan, Tolunay & Uma, 2001). One tissue in which such NANC relaxations have been identified is the guinea‐pig PA (Maggi et al.…”
Section: Introductionmentioning
confidence: 99%